ECONOMIC CONSTANT OF INTRODUCING RESOURCE-SAVING TECHNOLOGIES AT A CONSTRUCTION COMPANY IN AN UNSTABLE MARKET ENVIRONMENT WITH LIMITED RESOURCES - Руслан Кубанов; Дмитро Макатьора; Дмитро Прусов (Економіка та суспільство, 2024)
Theoretical concepts and applied possibilities concerning the feasibility of introducing resource-saving technologies in a construction company under the influence of an unstable market environment and limited resources are determined. The article considers the dependence of construction production on many factors of the external and internal environment: natural and climatic, engineering and geological, economic, suppliers, sub-suppliers. This leads to the existence of a variety of projected cost and time indicators for a given construction project. This is due to the impossibility of obtaining accurate information on the conditions of project implementation. In the authors’ opinion, the limited availability of raw materials and the threat of their depletion are the reason for the constant rational use of raw materials and the search for new energy sources. The authors argue that in an unstable market environment and with limited resources, introducing resource-saving technologies can have a significant economic impact. Economic benefits, reduction of negative impact on the environment, improvement of the company’s image and status are the main advantages of introducing such technologies. It is necessary to compare the economic benefits of implementing resource-saving technologies with the costs of their installation and operation in order to determine the economic feasibility constant. Economic benefits include increased productivity, reduced costs due to resource savings and improved product quality. Costs are related to the installation of new technology, replacement of equipment, staff training and other factors. Economic feasibility is an economic assessment that helps determine whether introducing resource-saving technologies is economically viable. It can help construction companies make decisions about investing in new technologies in the context of an unstable market environment and limited resources. The article gives examples of the use of cost-effective resource-saving technologies: the reconstruction of Maidan Nezalezhnosti (Independence Square) – the use of inventory shuttering in the complex use of softeners and chemical additives to concrete; the rationale for types of individual housing construction using recycled materials and the introduction of energy-saving technologies; the concept of “smart building”; the use of recycled materials such as bottles, paper, plastic and other materials in the construction of buildings. The article concludes that the use of resource-saving technologies can be an effective tool for ensuring the competitiveness and sustainable development of a construction company in an unstable market environment and with limited resources.